PWE-139 Further Validation of Terminal Peptide of Procollagen Iii (PIIINP) for the Detection and Assessment of Nonalcoholic Steatohepatitis in Patients with Nonalcoholic Fatty Liver Disease. (4th June 2013) - Tanwar, S; Parkes, J; Hogan, B J; Schuppan, D; Pinzani, M; Arthur, M J P; Burt, A; Rosenberg, W M
Abstract : Introduction: PIIINP has recently been shown to discriminate between simple steatosis (SS) and NASH both in patients without advanced fibrosis and in patients with all degrees of fibrosis 1 . In this study we validated PIIINP as a biomarker of NASH in a cohort of patients with biopsy proven NAFLD and evaluated its performance at the proposed diagnostic thresholds. Methods: 71 patients with NAFLD and no evidence of other liver disease were included in this study. Liver biopsies were performed on all patients and analysed by a expert liver histopathologist. All liver biopsies were of suitable size for analysis (> 12mm and > 5 portal tracts) and classified in a dichotomous manner into those with SS or histological NASH. Fibrosis was assessed using the Scheuer classification. Serum samples were taken at the time of liver biopsy. Results: 14 of the 60 patients with non-advanced fibrosis (4-F0, 18-F1.1-F2) and all 11 patients with advanced fibrosis (9-F3, 2-F4) had NASH respectively. The AUROC of PIIINP in discriminating between SS and NASH in patients with non-advanced fibrosis and all degrees of fibrosis was 0.81 (CI 0.69–0.94) and 0.87 (CI 0.79–0.96) respectively. In comparison, the ability of ALT to discriminate between SS and NASH ranged between 0.43–0.45. The performance of the recently proposed thresholds PIIINP in their ability to diagnose NASH in our population is displayed in the table . Conclusion: PIIINP discriminates between SS and NASH. The performance of the proposed diagnostic thresholds is comparable to that reported in the original publication of this biomarker. Our results suggest that PIIINP can be used to detect the minority of patients with NAFLD who have NASH and are at risk of developing progressive fibrosis. Disclosure of Interest: None Declared. Reference: Tanwar S et al. Validation of Terminal Peptide of Procollagen III for the Detection and Assessment of Nonalcoholic Steatohepatitis in Patients with Nonalcoholic Fatty Liver Disease. Hepatology. 2013 Jan; 57(1):103–11. doi: 10.1002/hep.26030. PMID: 22930399